2017
DOI: 10.5539/jel.v7n1p208
|View full text |Cite
|
Sign up to set email alerts
|

Student Teachers’ Proactive Strategies and Experienced Learning Environment for Reducing Study-Related Burnout

Abstract: The study aims to gain a better understanding of the interrelation and the development of student teachers’ proactive coping strategies, i.e., self-regulative and co-regulative strategies, perceived learning environment and study-related burnout. Longitudinal data were utilized with three annual measurements during bachelor studies. Altogether, 270 primary school student teachers completed the survey. The data was analyzed by using Structural Equation Modeling (SEM). Results showed that the self-regulative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
(116 reference statements)
1
7
0
Order By: Relevance
“…The validity and reliability of the scales used in this study and the tested two-level path model were acceptable (Bollen, 1989;Hu & Bentler, 1999). As previous studies have shown (Pietarinen et al, 2013a;Pyhältö et al, 2021;Väisänen et al, 2018aVäisänen et al, , 2018b, the developed proactive strategy (SELF-REG α = .84; CO-REG α = .62) and burnout scales (EXH α = .81; CYN α = .77; INAD α = .74) sufficiently specified the social contexts of experienced cynicism and sense of inadequacy in teachers' work at the individual teacher level. This study, in turn, showed that the burnout scale (EXH α = .83; CYN α = .71; INAD α = .71) and the further developed proactive strategy scale, in terms of co-regulative strategy measurement (SELF-REG α = .85; CO-REG α = .88), can be used for identifying school-level differences related to proactive regulation of the burnout symptoms in the professional community.…”
Section: Methodological Considerationssupporting
confidence: 55%
See 3 more Smart Citations
“…The validity and reliability of the scales used in this study and the tested two-level path model were acceptable (Bollen, 1989;Hu & Bentler, 1999). As previous studies have shown (Pietarinen et al, 2013a;Pyhältö et al, 2021;Väisänen et al, 2018aVäisänen et al, , 2018b, the developed proactive strategy (SELF-REG α = .84; CO-REG α = .62) and burnout scales (EXH α = .81; CYN α = .77; INAD α = .74) sufficiently specified the social contexts of experienced cynicism and sense of inadequacy in teachers' work at the individual teacher level. This study, in turn, showed that the burnout scale (EXH α = .83; CYN α = .71; INAD α = .71) and the further developed proactive strategy scale, in terms of co-regulative strategy measurement (SELF-REG α = .85; CO-REG α = .88), can be used for identifying school-level differences related to proactive regulation of the burnout symptoms in the professional community.…”
Section: Methodological Considerationssupporting
confidence: 55%
“…The use of co-regulative strategies was associated with reduced levels of cynicism toward the teacher community and sense of inadequacy in teacher-pupil interaction, whereas self-regulative strategies were only effective in reducing teacher exhaustion. In our recent study, we showed that proactive strategy use was also associated with reduced risk of pre-service teacher burnout during teacher education, particularly in terms of experienced exhaustion and sense of inadequacy in studying (Väisänen et al, 2018a(Väisänen et al, , 2018b. In turn, a lack of reciprocity in social relationships and support at work has been found to be related to increased levels of experienced burnout among teachers (A.…”
Section: Proactive Strategies In Teacher's Workmentioning
confidence: 99%
See 2 more Smart Citations
“…It is noteworthy that this provision is typical for university teachers and other developed countries. Despite the fact that there are practically no studies concerning the social component of a teacher's activity, nevertheless, a high correlation is established between the availability of information and the emotional support for young teachers by their colleagues and the emergence of various burdens in psychological well-being (Väisänen et al, 2017).…”
Section: Resultsmentioning
confidence: 99%